Модель отказоустойчивой маршрутизации многоадресных потоков в телекоммуникационных сетях - Лемешко, О. В.; Арус, К. М. (ХНУРЭ, 2013)
Flow models of multicast and broadcast routing in telecommunications networks are proposed. The novelty of models lies in description of multiproduct case, as well as in consideration of flowing nature of modern network traffic, allowing to implement previously known conditions for prevent communicati on channels overload prevention for the case of multicast and broadcast routing type. The models are represented by a system of linear equations and inequalities, which makes them quite effective in terms of computer implementation. As part of the proposed models, problems of multicast and broadcast routing are focused on solving optimization problems of Boolean programming. The example shows efficiency of the proposed models in terms of service simultaneously multiple traffics with different characteristic s, models adaptation to changes in network parameters (channel capacity). The proposed model can be used directly for solving the broadcast and multicast routing problems, and the mathematical description of more complex processes and problems, such as those associated with the design of telecommunications networks, where routing problem complement other important network tasks (selection of topology and bandwidth of communication channels). Design of flow - based model for MPLS Fast ReRoute is proposed in the paper. The model allows for the same flow calculate two types of paths: primary and backup. Depending on the parameters of the model it is possible to implement different schemes of reservation: link, node or path protection. In the course of solving the problem of MPLS Fast Reroute the classical metric of primary and backup paths is minimized. The nonlinear restrictions, which are responsible for prevention of node, link or path interse ction of primary and backup routes is introduced in the structure of the model.